Menggali Potensi Pembelajaran Dalam Pendidikan Non Formal: Alat-Alat Pendidikan Untuk Mendukung Kreativitas Peserta Didik - Difa Salsabila Putri; Elvara Adelia; Merisa Merisa (Politeknik Kampar, 2024)
Non-formal education has an important role in improving the quality of human resources. However, to achieve this goal, educational tools are needed that can support the creativity of students. This article discusses educational tools that can be used to support the creativity of students in non-formal education. Some of the educational tools covered include verbal and figural creativity tests, non-formal education programs that focus on the needs and interests of learners, practical exercises, effective learning methods, and information technology. Not only that, the use of educational tools needs to pay attention to steps that are appropriate for their purpose. By paying attention to this, educators can support the creativity of students and help them develop skills and knowledge necessary for everyday life. This article is expected to contribute to the development of non-formal education in Indonesia.